2002
DOI: 10.3168/jds.s0022-0302(02)74271-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Forage Particle Size and Grain Fermentability in Midlactation Cows. II. Ruminal pH and Chewing Activity

Abstract: Our study investigated the effects of, and interactions between, level of dietary ruminally fermentable carbohydrate (RFC) and forage particle size on rumen pH and chewing activity for dairy cows fed one level of dietary NDF. Also, correlations between intake, production, chewing, and ruminal pH parameters were investigated. Eight cows (61 days in milk) were assigned to four treatments in a double 4 x 4 Latin square. Treatments were arranged in a 2 x 2 factorial design; finely chopped alfalfa silage (FS) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
168
12
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(216 citation statements)
references
References 22 publications
31
168
12
5
Order By: Relevance
“…In the present study, ruminal pH was above the benchmark for subacute ruminal acidosis (pH >5.6), but a depression of ruminal pH <6 is already associated with irregular patterns of feed consumption during the day resulting in decreased feed intake (Krause et al, 2002;Gimeno et al, 2015). A larger barley grain PS also resulted in increased glucose concentration in blood.…”
Section: Discussioncontrasting
confidence: 41%
“…In the present study, ruminal pH was above the benchmark for subacute ruminal acidosis (pH >5.6), but a depression of ruminal pH <6 is already associated with irregular patterns of feed consumption during the day resulting in decreased feed intake (Krause et al, 2002;Gimeno et al, 2015). A larger barley grain PS also resulted in increased glucose concentration in blood.…”
Section: Discussioncontrasting
confidence: 41%
“…An increase in total saliva secretion may improve rumen buffering, preventing a decline in rumen pH and potentially reducing the risk of ruminal acidosis . Krause et al (2002) observed that pH decreased when geometric mean particle length (X gm ) of alfalfa silage decreased from 13.6 to 3.7 mm (fed at 39 : 61 forage to concentrate ratio, F : C).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the documented physiological importance of dietary PS, research has shown that the effects of forage PS are also dependent on the degradation characteristics of the diet (Krause et al, 2002a and2002b;Silveira et al, 2007). Several lines of evidence indicate that for the same forage PS in the diet, the physiological responses obtained are different when these diets are based on barley v. corn (Allen, 1997;Beauchemin and Rode, 1997;Lechartier and Peyraud, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Eating and ruminating activities were noted at 5-min intervals, and each activity was assumed to persist for the entire 5-min interval. A period of rumination was defined as at least 5 min of rumination occurring after at least 5 min without rumination (Krause et al, 2002b). A meal or period of eating was defined as at least one observation of eating activity occurring after at least 20 min without eating activity (Krause et al, 2002b).…”
mentioning
confidence: 99%
See 1 more Smart Citation